A New Hope: Theory, Rhetoric and the Conversation of Cinema. - Gorber, Jason L. (My University, 1999)
A New Hope: Theory, Rhetoric and the Conservation of Cinema
This thesis illustrates how both film theory and film criticism rely upon rhetorical devices which produce convincing arguments to ground their claims. By expanding Bordwell's rhetorical model of film criticism to film theorizing, it is hoped that we might rid the conservation of cinema of its more staid and dogmatic elements.
Without foundational truth as the regulator of discourse, totalizing theory can no longer be recognized as a healthy or adequate stance within the conservation of cinema. Carroll and Bordwell's respective projects do not rely upon foundational truth as a starting ground for analyses, criticisms, and theories of film.
With its competing uses of similar truth 'cues', the theoretical and critical conservation of cinema is governed by pragmati uses of rhetorical structures to make claims that are convincing to the reader.
Keywords: theory; conservation; cinema; Bordwell; rhetorical model; criticism; Film and Media Studies; Philosophy; Film and Media Studies